Respostas
respondido por:
4
Chamando os números de a e b, temos:
(a - b)³ = (a - b) (a - b)²
= (a - b) (a² - 2ab + b²)
= a.a² + a.(-2ab) + a.b² -b.a² -b.(-2ab) -b.b²
= a³ - 2 a²b + ab² -a²b +2ab² - b³
= a³ -3a²b +3ab² - b³
(a - b)³ = (a - b) (a - b)²
= (a - b) (a² - 2ab + b²)
= a.a² + a.(-2ab) + a.b² -b.a² -b.(-2ab) -b.b²
= a³ - 2 a²b + ab² -a²b +2ab² - b³
= a³ -3a²b +3ab² - b³
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás